(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2017)
The construction of a sustainable building in Indonesia has increased in recent years. Middle- to high-rise buildings are encouraged to enhance its performance to reduce energy demands. With maximum temperature 34°C, most of the buildings in Indonesia utilize mechanical air conditioning to achieve indoor thermal comfort. In this research, the performance of campus building with Double Skin Façade (DSF) in Indonesia would be quantitatively assessed and simulated by utilizing Autodesk Revit and Green Building Studio. In respect to façade material, actual cavity width, inner and outer layer façade type, and also weather condition, these simulations are expected to produce comparison result between four DSF material configurations which are perforated metal, single glazing, double glazing, and triple glazing. From the simulation, the results show that perforated metal DSF could consume 5%-23.16% more energy for space cooling compared to building with glass DSF.